Determination of Triclabendazole by Visible Spectrophotometry - Mruthunjaya Rao, R.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple, accurate rapid and sensitive reproducible visible spectrophotometric methods (A-C) have been developed for the estimation of triclabendazole in pure and pharmaceutical dosage forms. Methods A and B are based on the formation of chloroform soluble ion-association complex formation under specified experimental conditions are described. method C is based on the oxidative coupling under specified experimental conditions are described. Two acidic dyes, wool fast blue BL (WFBBL, λmax 580 nm method B) tropaeolin OOO (TPOOO, λmax 480 nm, method A) are utilized. Method C (λmax 520 nm) is based on the reaction of drug with brucine and sodium metaperiodate under acidic conditions forming coloured bruciquinone derivatives. Results of the analysis for these methods were validated statistically by recovery studies.